Konsep Amanah dalam Pengelolaan Uang: Kajian Tematik atas QS An-Nisa’ 5, An-Nisa’ 29, dan Al-Baqarah 177 - Ahkamil Hakim; Nurhayati; Yenni Samri Juliati Nasution (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This study aims to explore the meaning of trust in financial management based on Surah An-Nisa' 5, Surah An-Nisa' 29, and Surah Al-Baqarah 177 through a focused thematic interpretation (maudhu'i intiqā'i) approach. By examining three key relevant verses, this study emphasizes the principle of prudence, the prohibition on misuse of wealth, and social responsibility in financial management. The analysis was conducted qualitatively through a review of classical and contemporary exegetical literature, as well as content analysis to identify the ethical values ​​and legal principles contained. The results indicate that trust encompasses the dimensions of personal integrity and transparent and accountable professional governance. Wealth is not only the property of the individual but also a means for societal welfare and distributive justice. These findings contribute to the development of an economic system with integrity, justice, and a focus on social benefits.